2003
DOI: 10.1038/sj.gene.6363911
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of HLA/TNF region is linked to leprosy clinical spectrum in families displaying mixed leprosy subtypes

Abstract: Each year an estimated 600 000 new leprosy cases are diagnosed worldwide. The spectrum of the disease varies widely from limited tuberculoid forms to extensive lepromatous forms. A measure of the risk to develop lepromatous forms of leprosy is provided by the extent of skin reactivity to lepromin (Mitsuda reaction). To address a postulated oligogenic control of leprosy pathogenesis, we investigated in the present study linkage of leprosy susceptibility, leprosy clinical subtypes, and extent of the Mitsuda reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…10 HLA was identified as a positive region of linkage in the Vietnamese 8 but not the Indian 7 leprosy study. Further investigation of the Vietnamese population 16 indicates linkage to clinical sub-type, as many earlier studies (e.g. 17,18 ) had suggested.…”
Section: à7mentioning
confidence: 93%
See 1 more Smart Citation
“…10 HLA was identified as a positive region of linkage in the Vietnamese 8 but not the Indian 7 leprosy study. Further investigation of the Vietnamese population 16 indicates linkage to clinical sub-type, as many earlier studies (e.g. 17,18 ) had suggested.…”
Section: à7mentioning
confidence: 93%
“…As outlined in the legend to Table 2, nonparametric linkage analysis in ALLEGRO 12 that reports maximum Z scores for the likelihood ratio (Z lr ) and allele-sharing LOD scores 13 was used to analyse the genome scan linkage data. This analysis provided evidence at Po0.05 for linkage of susceptibility to 8 regions of the genome on chromosomes 2, 3, 7, 10, 11, 20, 21 and X (LOD scores 0.60 to 2.43; 1-sided p values 0.0004oPo0.048) for tuberculosis, and to 9 regions on chromosomes 6,9,11,12,13,15,16,17,20 (LOD scores 0.74 to 2.50; 1-sided P values 0.0003oPo0.033) for leprosy per se. For tuberculosis, 58 markers from the positive regions were typed in a second set of families (Table 1), with 22 additional markers typed in both family sets.…”
mentioning
confidence: 99%
“…During the first period (1998)(1999)(2000)(2001)(2002), we recruited patients with leprosy irrespective of the occurrence of T1Rs (hereafter, referred to as sample A). This sample has previously been used for a genetic study of leprosy [24,25]. During the second period (2002)(2003)(2004), we recruited only patients with leprosy who had experienced T1Rs (hereafter, referred to as sample B).…”
Section: Patientsmentioning
confidence: 99%
“…Differences in susceptibility can be genetic or caused by environmental factors that alter the health status of a person. Genetic studies found an association of both susceptibility to leprosy (Fitness et al, 2002;Mira et al, 2004;Zhang et al, 2009) and the type of leprosy e tuberculoid or lepromatous e with genetic factors (Mira et al, 2003). In an epidemiological study, Bakker et al (Bakker et al, 2005) found that approximately 50% of the susceptibility was explained by inheritance.…”
Section: Heterogeneity In Leprosymentioning
confidence: 97%